Inside the Expressive Culture of Chinese Women's Mosques: This Turmoil of the Soul - Jaschok, Maria (Routledge Contemporary China., 2025)
This book presents a multi-voice narrative of the history and significance of current contestations over the increasing prominence of expressive piety in Hui Muslim women’s mosques in central China. By drawing on a ‘Song Book’ of chants, collected from the tradition of women’s mosques, as context it reveals just how the increasing prominence of female voices has given rise to considerable misgivings among senior religious leaders over the potential destabilization of orthodox Islamic gendered practices. Providing a historical introduction to the place and function of Islamic chants,jingge and zansheng, the book gives a conceptual framing of female silence, sound, and agency in local translations of Confucian and Islamic precepts, and women’s personal accounts of the role played by traditional and modern soundscapes in transmitting and celebrating Islamic knowledge and faith. As a study of women's soundscapes and the significance of legitimacy, ambiguities, and implications of female sound, this book will be of considerable interest to students and scholars of Chinese society and culture, gender studies, cultural anthropology, and Islam.